2017
DOI: 10.5194/acp-17-11779-2017
|View full text |Cite
|
Sign up to set email alerts
|

CCN activity and organic hygroscopicity of aerosols downwind of an urban region in central Amazonia: seasonal and diel variations and impact of anthropogenic emissions

Abstract: Abstract. During the Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) campaign, sizeresolved cloud condensation nuclei (CCN) spectra were characterized at a research site (T3) 60 km downwind of the city of Manaus, Brazil, in central Amazonia for 1 year (12 March 2014 to 3 March 2015. Particle hygroscopicity (κ CCN ) and mixing state were derived from the size-resolved CCN spectra, and the hygroscopicity of the organic component of the aerosol (κ org ) was then calculated from κ CCN and conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 106 publications
9
79
2
Order By: Relevance
“…The highest individual correlation was with the ADOA factor loading (Adam Bateman, personal communication, 2017). In addition, Thalman et al (2017), also using the PMF results reported herein, concluded that the larger relative contribution of secondary organic material during the daytime compared with the nighttime was the primary driver of the diel trend of higher particle hygroscopicity during the day compared to the night, as tied to the properties of cloud condensation nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The highest individual correlation was with the ADOA factor loading (Adam Bateman, personal communication, 2017). In addition, Thalman et al (2017), also using the PMF results reported herein, concluded that the larger relative contribution of secondary organic material during the daytime compared with the nighttime was the primary driver of the diel trend of higher particle hygroscopicity during the day compared to the night, as tied to the properties of cloud condensation nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…at the T3 site (main GoAmazon site at Manacapuru; see Martin et al, 2016, for a detailed description). The data were averaged to 5 min intervals covering the period from January 2014 to March 2015 (Thalman et al, 2017). Background or polluted conditions were defined based on the specific CPC distribution for each season by the thresh-old value associated with the 33 and 66 % percentile, respectively, for the dry and wet seasons.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the leading techniques for detailed chem-ical characterization of the organic fraction of ambient particulate matter rely on particle collection-volatilization cycles (Williams et al, 2006;Lopez-Hilfiker, 2014). Other techniques that explore size-dependent properties of ambient (Mei et al, 2013;Thalman et al, 2017) or laboratorygenerated (Ahern et al, 2016;Petters et al, 2006;Vaden et al, 2011) organic aerosol using differential mobility analyzers (DMAs), such as Humidified Tandem DMA (HT-DMA) or cloud condensation nuclei counters (CCNCs), are complicated by the necessity of size selection of polydisperse samples, which work with a small mass fraction of a given aerosol sample's original population. Online (continuousflow) aerosol concentration would improve instrument signal and time response in these types of studies, simplifying data analysis.…”
Section: Introductionmentioning
confidence: 99%